Energy dissipation and damage evolution for dynamic fracture of marble subjected to freeze-thaw and multiple level compressive fatigue loading. (January 2021) - Wang, Y.; Gao, S.H.; Li, C.H.; Han, J.Q.
Highlights: Previous freeze-thaw damage influenced a lot on rock fracture and energy dissipation characteristics. Increasing rate of dissipated energy gets faster indicating high damage accumulation of rock. A F-T-fatigue loading coupling damage variable was put forward based on energy evolution analysis. A damage evolution model was established to describe the damage evolution for cyclic loading process. Abstract: For rock engineering in cold regions, rock is often subjected to coupled fatigue conditions of freeze-thaw (F-T) and stress disturbance. Rock fracture evolution and energy mechanism under room temperature and constant stress amplitude loading condition have been widely investigated. Yet the rock energy dissipation and damage evolution characteristics subjected to multiple level cyclic loading conditions are not well understood. In this work, multiple level cyclic compressive loading experiments were conducted using GCTS RTR 2000 rock mechanics system on marble with F-T treatment of 0, 20, 40 and 60 cycles. The fracture evolution and energy dissipation mechanism were analyzed as well as the damage evolution characteristics. The results indicate that F-T treatment strongly influences the fatigue mechanical behaviors of marble, with both fatigue strength and strain energy decreases and irreversible volumetric deformation increases with increasing F-T cycles. The incremental rate of dissipated energy becomes faster as cyclic loading level grows. In addition, a F-T-fatigue loads coupling damage variable was proposed by using the input total strain energy and the dissipated strain energy to describe the rock damage evolution after F-T treatment and experiencing fatigue loading. Moreover, a damage evolution model was first established based on the obtained coupling damage variable to describe the two-phase damage accumulation characteristics. Damage accumulation curve presents a first steady increase and then faster increase trend, the damage evolution model can good fit the experimental data.